EU Wholesale Trade: Analysis of the Sector and Value Chains - Ella Broos; Bernhard Dachs; Martina Dünser; Doris Hanzl-Weiss; Kristof Mertens; Doris Schartinger; Robert Stehrer; Valentijn Vanoeteren (The Vienna Institute for International Economic Studies (wiiw), 2016)
This report investigates wholesale as one of the main service industries in the European economy. Wholesale is the resale of new and used goods to retailers, industrial, commercial, institutional or professional users, or to other wholesalers on their own account or for third parties. It plays a pivotal role in the European Single Market by bridging national markets and connecting producers, retail trade and industrial demand across Europe. Wholesale employs about 10 million persons in the EU-28 and accounts for a share of 7-9% in total employment in most EU Member States. The share of micro and small enterprises is considerably higher than in manufacturing. The sector reveals considerable heterogeneity in terms of firm size, productivity and profitability across EU Member States and wholesale sub-sectors. Moreover, the report sheds light on the integration of the wholesale sector in value chains with upstream manufacturers and downstream retailers, and on the role of technology and innovation in wholesale.
Keywords: L16; L81; 330; wholesale; EU integration; value chains; services; innovation